MENGEKSPLORASI PARADOKS PRIVASI GEN-Z DALAM PERSONALISASI IKLAN DI MEDIA DIGITAL - Tania, Syaifa (Master of Communication Science Program, Universitas Diponegoro, 2023)
The practice of disclosing personal information in accessing digital media is inevitable. In digital transaction consumers are required to fill personal data in which quite risky, while the nature of social media facilitate user to willingly share their daily life. This condition leads to the discussion of personalization-privacy paradox that put digital media user in a dilemmatic position. In one hand, they enjoy the relevancy of personalized offerings otherwise they worry about the risk of disclosing information as the result digital media algorithm. This study is aimed to capture the personalizationprivacy paradox faced by the gen Z as the true digital natives using survey method. As the result of the study, personalization-privacy paradox is a real issue faced by respondents. They actively calculate the risk and benefit of sharing their information in digital platform. Moreover, they also tend to be less cautious towards popular digital application as they already consider it as a safe platform.